PEMEROLEHAN SINTAKSIS ANAK USIA LIMA TAHUN MELALUI PENCERITAAN KEMBALI DONGENG NUSANTARA - Impuni Impuni (Universitas Muhammadiyah Surakarta, 2012)
The objective of the reseach is to describe: (1) the syntactic acquisition of five-year-old children aged five years as they recount folktales, (2) the types of complex sentences they produced when telling the stories, (3) the frequency of simple and compound sentences they produced , and (4) the implementation of syntactic acquisition in early childhood. This reseach used a qualitative descriptive method. The techniques of data collection used were interviewing, recording, and note-taking. The test validity of the data source was triangulation technique. The data-analyzing technique was Direct Elemental Division (BUL) and strengthened by the Changing Form technique. The reseach concludes that the acquisition of simple and compound sentences conformed with the development stage of their age. The use of one word and two words were often produced by children. They also used the passive voice when recounting the tales. They used the verb suffix di- and di-in. Acquisition of syntax through recounting tales can be applied in accordance with existing standards of competency.